TRANSFORMASI DIMENSI KEHIDUPAN SRIKANDI DALAM NOVEL KEKASIH MUSIM GUGUR KARYA LAKSMI PAMUNTJAK - Nadhila Hibatul Nastikaputri; Sudibyo Prawiroatmodjo (HISKI, 2022)
Kekasih Musim Gugur is a contemporary Indonesian fiction work that contains elements of traditional literary stories in the form of wayang (Indonesian shadow puppetry) tales. Based on the initial reading of the novel Kekasih Musim Gugur, several similarities in the portrayal of the main character, Srikandi Eilers, in the novel with the character of Srikandi in Javanese wayang were found. This research aims to describe the forms of transformation of wayang story elements in various dimensions of the life of the character Srikandi Eilers in the novel Kekasih Musim Gugur using the concept of intertextuality by Julia Kristeva. Through the analysis, it is revealed that the most prominent transformation in this novel is the transformation of character elements. Character transformation in this novel takes the form of naming and characterization transformations. The naming transformation model is applied to all the names of the main characters in the novel. Meanwhile, the characterization transformation model is applied to some of the main character's personas in the novel through three dimensions of the character's life: (1) Srikandi as Amba's child; (2) Srikandi as a stepmother; and (3) Srikandi as a bisexual woman. The transformation of characters is adapted by the author to the social context at the time when Kekasih Musim Gugur was written. By transforming the name of the wayang character Srikandi into the character of Srikandi Eilers, the author simultaneously transforms several aspects of her character. Therefore, the transformation of naming in the novel Kekasih Musim Gugur shows a typological tendency (naming based on a person's personality or character).AbstrakKekasih Musim Gugur merupakan karya fiksi Indonesia kontemporer yang di dalamnya mengandung unsur karya sastra lama berupa cerita pewayangan. Berdasarkan pembacaan awal terhadap novel Kekasih Musim Gugur, ditemukan adanya sejumlah kesamaan penggambaran Srikandi Eilers sebagai tokoh utama dalam novel tersebut dengan tokoh Srikandi dalam pewayangan Jawa. Penelitian ini bertujuan mendeskripsikan bentuk-bentuk transformasi unsur cerita pewayangan pada sejumlah dimensi kehidupan tokoh Srikandi Eilers dalam novel Kekasih Musim Gugur dengan menggunakan konsep teori intertekstualitas Julia Kristeva. Berdasarkan analisis, diketahui bahwa transformasi yang paling menonjol di novel ini adalah transformasi unsur penokohan. Transformasi penokohan dalam novel ini mengambil model transformasi penamaan dan perwatakan. Model transformasi penamaan dilakukan pada seluruh nama tokoh utama dalam novel. Sementara, model transformasi perwatakan dilakukan pada sebagian karakter tokoh utama novel melalui 3 dimensi kehidupan tokoh, yakni (1) Srikandi sebagai anak Amba; (2) Srikandi sebagai ibu tiri; dan (3) Srikandi sebagai perempuan biseksual. Pentranformasian karakter disesuaikan oleh penulis dengan konteks sosial saat Kekasih Musim Gugur dituliskan. Dalam melakukan transformasi nama tokoh wayang Srikandi pada diri Srikandi Eilers, penulis sekaligus mentransformasikan sejumlah karakternya. Dengan demikian, pentransformasian penamaan dalam novel Kekasih Musim Gugur menunjukkan kecenderungan tipologis (penamaan berdasarkan watak atau karakter seseorang).